Examination on The Last Will of Organs and Cadaver Donors Related to Health Omnibus Law of Indonesia - Narwastuty, Dian; Yuniawaty, Yenny; Basani, Christin Septina (Journal of Contemporary Law Studies, 2024)
This study aims to analyze the role of the last will in organ and cadaver donations within the framework of Indonesia's Health Omnibus Law. Utilizing a normative juridical approach, the research examines legal principles and regulations, emphasizing the significance of last wills as legal documents to streamline donation procedures, clarify donor intentions, and safeguard rights. Data was collected from legal texts, government publications, and expert interviews to identify gaps in the legal system, focusing on donor autonomy and family consent.The findings reveal ambiguities in implementing last wills, often leading to conflicts with family consent and religious considerations. Interviews with legal and healthcare professionals indicate the prioritization of family decisions over documented donor wishes, highlighting the need for clear guidelines and legal safeguards. The study also identifies logistical and cultural challenges, including low public awareness and inadequate healthcare infrastructure, which hinder the effective implementation of organ donation laws.This research concludes that integrating last wills into Indonesia's legal framework can enhance procedural transparency, protect donor rights, and address ethical and cultural complexities. Revisions to existing regulations, public education, and improved healthcare infrastructure are recommended to balance donor autonomy with societal and health system needs, ensuring a robust organ donation system.